Distribution of Heavy Metals Found in Three Major Rivers of North-Eastern Pulau Langkawi - Richard C. S, Wong; Chun Foong, Chan; Hong Wee, Wong (Malaysian Journal of Science, 2005)
A preliminary study on the distribution of dissolved heavy metals such as Cu, Cd, Fe, Pb and Zn in seawater were carried out along the three major rivers of Air Hangat, Kilim and Kisap located in north-eastern Pulau Langkawi. Samples were collected from a total of nine selected stations located along these rivers where salinity ranges from 32-36 ppt. Almost all elements showed little variation in concentration along the stretches of the rivers to the open sea. This indicates that their distributions in the coastal area are not regulated by dilution with open seawater. The concentrations of Cu, Cd, Fe, Pb and Zn showed negative correlations with salinity. The low level detection for the metals Cu, Fe, Pb and Zn except for Cd, most probably indicates that it is of a naturally occurring source.